2022
DOI: 10.3390/ma15144784
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impacts of Green Synthesized Silver Nanoparticles on Maerua oblongifolia Shoots under In Vitro Salt Stress

Abstract: Salinity is one of the major abiotic stresses that affect the plant’s growth and development. Recently, the contribution of nanoparticles (NPs) to ameliorating salinity stresses has become the new field of interest for scientists due to their special physiochemical properties in the biological system. This study is designed to examine the effects of biosynthesized silver nanoparticles (AgNPs) spherical in shape (size range between 9 and 30 nm) on morphophysiological characteristics and the antioxidant defense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
4
6
0
Order By: Relevance
“…Moreover, inadequate nutrient uptake by plants or increased Na + translocation to the shoots might be a reason for decreasing tomato plant growth under salinity (Sha et al, 2010;Hussein et al, 2015). Similar to the present data, previous studies on maize (Omoto et al, 2009), sorghum (Netondo et al, 2004), Oenanthe javanica (Kumar et al, 2021), Sapium sebiferum (Shah et al, 2020), and Maerua oblongifolia (Shaikhaldein et al, 2022) revealed that photosynthetic component and plant growth decreased when exposed to salinity. It is interesting that, using ethylene inhibitors such as AgNO 3 and PZA showed favorable effects on the growth features of tomato plants under in vitro salt treatments and dramatically reduced the negative impacts of salinity.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, inadequate nutrient uptake by plants or increased Na + translocation to the shoots might be a reason for decreasing tomato plant growth under salinity (Sha et al, 2010;Hussein et al, 2015). Similar to the present data, previous studies on maize (Omoto et al, 2009), sorghum (Netondo et al, 2004), Oenanthe javanica (Kumar et al, 2021), Sapium sebiferum (Shah et al, 2020), and Maerua oblongifolia (Shaikhaldein et al, 2022) revealed that photosynthetic component and plant growth decreased when exposed to salinity. It is interesting that, using ethylene inhibitors such as AgNO 3 and PZA showed favorable effects on the growth features of tomato plants under in vitro salt treatments and dramatically reduced the negative impacts of salinity.…”
Section: Discussionsupporting
confidence: 92%
“…The scanning electron microscope (SEM) showed nanoparticle silver, spherically shaped, with a difference in size, with a AgNPs size rate of 48.31 nm. This study is consistent with Shaikhaldein et al [22] if the particles formed are spherical.…”
Section: Sem Analysissupporting
confidence: 93%
“…The TEM image shows that the AgNPs have a spherical shape with a size ranging from 21 to 26 nm. The result obtained by [42] showed that the AgNPs biologically synthesized using Ochradenus arabicus extract were spherical in shape with a size ranging between 9 and 30 nm. The nanoparticles' size depends on the plant species and the source of extracts that are used as reducing and capping agents.…”
Section: Discussionmentioning
confidence: 99%